2020
DOI: 10.1109/access.2020.2964630
|View full text |Cite
|
Sign up to set email alerts
|

Software-Based Video–Audio Production Mixer via an IP Network

Abstract: Modern television production has promoted the simultaneous use of several cameras and sound sources, which increases the complexity and costs of broadcasting studios. This paper describes the design and implementation of a video-audio production mixer via an IP network. It is presented as a potential replacement for traditional professional production systems on the basis of cost reduction, as it is a software-based system that uses the existing technologies and can be built in community television stations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Today, broadcasters use a specialized hardware appliance called vision-mixer to achieve this functionality. This functionality, however, can also be realized in a software running on a COTS server [21]. The production quality visionmixer has been implemented using open source tools like OBS studio and KX studio running on a generalpurpose platform.…”
Section: B Virtualized Media Processingmentioning
confidence: 99%
“…Today, broadcasters use a specialized hardware appliance called vision-mixer to achieve this functionality. This functionality, however, can also be realized in a software running on a COTS server [21]. The production quality visionmixer has been implemented using open source tools like OBS studio and KX studio running on a generalpurpose platform.…”
Section: B Virtualized Media Processingmentioning
confidence: 99%
“…D. Luzuriaga et al have also demonstrated the PoC for a vision mixer based on open-source software tools (e.g., OBS studio and KX studio) running on a COTS hardware platform [13]. They presented a low-cost replacement for a specialized hardware production system.…”
Section: Related Workmentioning
confidence: 99%
“…This ongoing transition to IP systems enables broadcasters and service providers to reduce their costs, and use their networks more efficiently [3][4][5]. It also permits to achieve higher operational flexibility and density using either software-based or cloud infrastructures [6][7][8][9]. To support all these efforts, the Society of Motion Picture and Television Engineers (SMPTE) has developed the SMPTE ST 2110 Suite of Standards [10], and a family of related standards known as SMPTE ST 2022 [11][12][13][14][15][16][17] specifying how to send digital audiovisual content over IP networks.…”
Section: Introductionmentioning
confidence: 99%